Âsâr-ı Celâl - Mehmed Celâl, 1867-1912. Unar, Salih Sâim, İmamızade, 1867-1965. Gülnar Hanım [Madam de Lebedev], 1854-?. Katırcıoğlu, Mahmud Muhtar, Paşa, 1867-1935. Mehmed Tâhir b. Rif'at, Bursalı, 1861-1925. Hüseyin Agâh. (İstanbul)
104 s.